Neglected Retained Central Venous Catheter Guidewire Complicated With Guidewire Rupture During Retrieval Process And Its Bailout Technique - Mohd Ab Hakim Ibrahim; Mohd Hafizuddin Husin; Nasibah Mohamad; Bazli Md Yusoff; Nadarajan, Chandran; Abdullah, Mohd Shafie (The Interventionalist Journal, 2022)
Central venous catheter insertion is a commonly performed procedure. This catheter is used to administer drugs and fluid, especially in critically ill patients, and monitor central venous pressure. We present a case of a retained guidewire for 17 months which was found incidentally from the abdominal and chest radiograph. We retrieved the retained J-tip guidewire using four loops retrieval snare. The retrieval process was complicated with the rupture of the guidewire, causing the unwinding of its outer sphere, leaving the inner monofilament dangling in the heart chamber. In this case report, we would like to describe the initial retrieval technique, which was failed and its bailout procedure.